Foreign direct investment, trade and economic growth: a new paradigm of the BRICS - Prabhakar, Akhilesh Chandra; Azam, Muhammad; Bakhtyar, Bardia; Ibrahim, Yusnidah (Canadian Center of Science and Education, 2015)
The present study begins by surveying broadly supports the assertion that regional integration in the case of the BRICS is not adequately paid attention except with very few original or significant contributions.This research examines the existing pattern in the areas of trade and investment with a view to locate in the development context.It was also essential to make a theoretical investigation on literature of trade along with the empirical one.The survey broadly supports the frequent, through usually undocumented, assertion that BRICS was an area had tended to neglect and to which they had made few if any original or significant contributions. Alongside, this study panel data on BRICSs, where the results confirm that foreign direct investment (FDI), trade and economic growth indicate the presence of long-run sustainable equilibrium relationship between them.It is thus important that policymakers to remove obstacles to FDI inflows and improve the respective absorptive capacity in order to reap maximize positive growth effects.This study also discussed that how China performed well through attracting FDI inflows and maintained trade balance.